Rh(I)-Catalyzed Intramolecular [3+2] Cycloaddition of trans-2-Allene-Vinylcyclopropanes - Liu, Cheng-Hang; Yu, Zhi-Xiang (Synlett, 2018)
An intramolecular [3+2] cycloaddition of trans-2-allene-vinylcyclopropanes for the synthesis of bicyclo[3.3.0]octane derivatives is developed.
Keywords: allenes; vinylcyclopropanes; rhodium; [3+2] cycloaddition; bicyclo[3.3.0]octanes